2017
DOI: 10.1097/fjc.0000000000000497
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection by Low-dose of Estrogen and Testosterone at the Physiological Ratio on Ovariectomized Rats During Ischemia/Reperfusion Injury

Abstract: Although estrogen and testosterone deficiency have often been associated with the development of cardiac diseases in postmenopausal women, the benefits of estrogen or testosterone therapy are controversial. Supplementation with high dose of estrogen or testosterone alone has been associated with many side effects, especially estrogen. This study was aimed to investigate whether supplementation of testosterone in combination with low-dose estrogen conferred stronger cardioprotective effects on ovariectomized ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Additionally, estrogen plays a positive role in the cardiovascular system and affects the blood perfusion of the heart (3,59). In agreement with other researchers, we showed that E2/ERs regulate ␤-ARs and protect female rat hearts subjected to isoprenaline (Iso)-induced heart failure or ischemia-reperfusion injury (37,75,135,155).…”
Section: Estrogen and Estrogen Receptorssupporting
confidence: 91%
“…Additionally, estrogen plays a positive role in the cardiovascular system and affects the blood perfusion of the heart (3,59). In agreement with other researchers, we showed that E2/ERs regulate ␤-ARs and protect female rat hearts subjected to isoprenaline (Iso)-induced heart failure or ischemia-reperfusion injury (37,75,135,155).…”
Section: Estrogen and Estrogen Receptorssupporting
confidence: 91%
“…A variety of tissues express estrogen receptors, including, intestine, brain, bone and adipose tissue [25]. As a result of this global expression, estrogen has been shown to influence a variety of physiological responses including neural development [29], cardiovascular health [16], bone density [30] and neoplastic diseases including cancers [12,13,15,31]. During menopause a variety of negative Fig.…”
Section: Physiological Role Of Estrogenmentioning
confidence: 99%
“…It is widely accepted that estrogen plays a significant role in many disease states including gynecologic conditions and cancers in addition to less obvious estrogen-mediated diseases such as metabolic syndrome ( Fig. 1) [12][13][14][15][16][17]. This review will demonstrate the influence the gut microbiome has on estrogen, and therefore estrogen-mediated disease, and related health outcomes (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of ERβ (Hsieh et al, 2015 ) and GPER (Wang et al, 2017 ) also reduced autophagy and apoptosis via PI3K pathway activation. Less information is available on the effects of testosterone, but there is data to suggest that it also modulates the PI3K response following injury (Huang et al, 2010 ; Fu et al, 2017 ). In addition, estradiol can regulate autophagy through interaction with adenosine monophosphate-activated protein kinase (AMPK).…”
Section: Sex and Autophagy Disruption In Alzheimer's Diseasementioning
confidence: 99%